BPB Option in Operative Fixation of Distal Radius Fracture - Nichols, Emma Hitt (MD Conference Express, 2014)
About 16% of all fractures treated by orthopaedic surgeons are of the distal radius, and the most common procedure used for their treatment is open reduction and internal fixation. Data from Brachial Plexus Block in Post-Op Pain Control After Distal Upper Extremity Fracture: A Prospective, Randomized Study [NCT01968824] compared the use of general anesthesia and brachial plexus blockade. Results are discussed in this article.